COMPARATIVE ANALYSIS OF COCOA CERTIFICATION AND NON-CERTIFICATION FARMING IN KELAPA DUA VILLAGE, ANREAPI DISTRICT, POLEWALI MANDAR REGENCY - Muh. Arman Yamin Pagala; Megawati (AgriDev, 2023)
Cocoa is one of the plantation crops that is widely cultivated in Polewali Mandar, the cocoa certification program is an effort to increase cocoa production and prices at the farm level. This study aims to determine the comparison of the income level of cocoa farms through the cocoa certification program and farms that have never participated in the certification program while developing the cocoa commodity, as well as to determine the comparison of R/C ratio and B/C ratio values. The implementation of this research began in May to July 2021, in Kelapa Dua village. Data collection techniques used structured interviews using questionnaires and question and answer. The results showed that the average income achieved by certified cocoa farmers is Rs 5,572.75 per/ha. When compared to the average income of non-certified cocoa farmers is Rs 4,715,429 per/ha. The difference between the income of certified and non-certified cocoa farmers is Rp. 857,325. The results of the R/C ratio analysis for certified cocoa can be planted by looking at the R/C ratio value of 2.40 and for non-certified cocoa has an R/C ratio value of 2.27. Profit B/C ratio result as a result of certified and non-certified income is 3.12. This shows that both certified and non-certified cocoa are feasible to develop, but certified cocoa has a greater income than non-certified cocoa.